Musique à l'école : des projets affiliatifs et interculturels au service du Projet Éducation 2030 de l'OCDE - François Joliat; Pascal Terrien (Université de Provence, 2021)
The OECD has published Future of Education and Skills: Education Project 2030. This report provides 36 key concepts for building the "transformative" skills of future citizens. Music education in schools has always been an active part of the formation of future citizens. Which scientific concepts underlying school music education projects could be matched with the concepts of the Education 2030 Project in order for this discipline to contribute to the development of the "transformative" competences described in this report? We conduct an a priori categorical analysis of the 36 key concepts of the Education 2030 Project to identify the scientific domains and psychological functions to which they relate. We then detail how the affiliative function and the etic/universalist function of the Education 2030 Project correspond to the key concepts that underlie theories of music education in schools. Finally, we propose an analysis of ensemble singing practice (affiliative function) with students and an analysis of student training practice in intercultural music education (ethical/universalist function) to support our prospective study